Development of a peer mentoring program for graduate students - Dimaano, Judith Dyan F. (College of Education, University of the Philippines Diliman, 2017)
This study aimed to gather evidence for the effectiveness of peer mentoring in providing personalized support for UP graduate students. The emergent conceptual framework, in line with the four research questions pertained to the needs of graduate students, the significant increase in the wellness levels of the graduate student mentees after participating in peer mentoring and the insights from the participants about the elements of an effective peer mentoring program. The research method was both quantitative and qualitative in nature. Quantitative data was collected using (1) the Needs Assessment Questionnaire (NAQ) which was administered to 367 UP graduate students from six colleges and schools in the university; (2) the Five Factors of Wellness Inventory (5F-Wel) that gathered pretest and posttest wellness scores of the 38 mentees, from the UP College of Education; and (3) the Assessment of Peer Mentoring Relationship (APMR) that measured the levels of perceived psychosocial and career-related support by the 22 peer mentors, who were all Guidance Majors, and their mentees. Qualitative data came from transcribed Focus Group Discussions (FGD) with groups of peer mentors and groups of mentees. Within one semester, mentor-mentee pairs interacted conveniently through personal meetings combined with text messaging and asynchronous online communications through email and social networking sites. Descriptive analysis of the NAQ responses showed that more than half of the graduate student respondents have concerns related to academics, career and personal issues. Majority (67%) identified peer mentors as a possible source of support who could provide advice and guidance. Paired samples # test of the pretest and posttest wellness scores showed a significant increase in the wellness levels among the mentees by the end of the semester-long implementation of the Peer Mentoring Program. Finally, descriptive analysis of the APMR scores and through the thematic analysis of the FGD transcripts revealed that psychosocial support was given through the mentoring relationship. The APMR results showed that (1) listening skills, (2) sharing of personal experiences and (3) giving of encouragement are ways by which psychosocial support was experienced in the mentoring relationship. In terms of career-related support, mentees received assistance to (1) reduce risks that threatened them from advancing through their programs of study, (2) gain opportunities to learn new skills and (3) accomplish academic objectives. The FGD sessions revealed a rich narrative about the mentoring experience. - In conclusion, the study revealed five essential elements involved in developing and evaluating a Peer Mentoring Program, beginning with (1) needs assessment and followed by (2) invitation of program participants, (3) training and orienting a pool of peer mentors and mentees, (4) putting up a monitoring system and finally, (5) using appropriate outcome measures to evaluate the effectiveness of the program. Hence, this study contributed to fill-in the research gaps with regard to the design, implementation, and evaluation of a peer mentoring program for graduate students using an evidence-based approach. The benefits of having peer mentoring program such as this, enables the university to make use of the resources of its own student body in a collective effort to promote personal wellness among students and to build supportive interpersonal relationships within the academic community.